Voltage regulation in a smart distribution system incorporating variable renewable generation - Petintin, J. O. (2014)
Intermittency of variable renewable generation (VRG) requires time sequence analysis, over a defined interval, to adequately capture VRG characteristics. As the penetration level rises, connected VRGs inject as much energy as the existing resource permits. It is therefore, essential to develop a technique that maintains system voltage profile, and facilitates the smoother integration of VRGs into the grid. This paper describes an approach to coordinate the use of load tap changing (LTC) transformers and switched capacitors (SCs) to improve the system-wide voltage profile due to the penetration of VRGs. Unlike other approaches that tend to optimize the size and location of VRGs, to enhance the grid performance, the proposed approach contends with the status quo of the system, with the added VRGs of different sizes and locations, and administers LTCs and SCs to regulate the system voltage. The IEEE 123 test feeder is considered as the test system in this paper. The effectiveness of the proposed method is validated under various test cases through a time sequence analysis over 24-hourly simulation period. The corresponding voltage profile is analyzed under various penetration levels of solar PV.